Effects of music in the social development of the mentally handicapped in divine mercy mobile school of music and arts : a study - San Agustin, Zenaida R. (Manila : National University, 1997)
Through this study, educators and other people con-corned on their plight and the stigma that they receive, may gain additional insights on the formulation and revision of programs that may contribute to the social development of mentally-handicapped children.
Approval Sheet -- Acknowledgement -- List of tables -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature -- Chapter 3. Methodology of the study -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices.
Research Method : Descriptive Method.
Includes bibliographical references.